2020
DOI: 10.1155/2020/6907395
|View full text |Cite
|
Sign up to set email alerts
|

Individual- and Community-Level Determinants for Complete Vaccination among Children Aged 12-23 Months in Ethiopia: A Multilevel Analysis

Abstract: Background. Childhood vaccination continues to increase dramatically. In spite of the success of immunization programs to date, millions of children continued to die each year, and sub-Saharan Africa (SSA) accounted for the world’s highest neonatal deaths. Childhood vaccination was designed as one of the most effective ways to reduce child mortalities from fatal vaccine-preventable diseases. Therefore, this study is aimed at investigating the individual- and community-level determinants of childhood complete v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 31 publications
(28 reference statements)
11
18
1
Order By: Relevance
“…The scatter plot results show that the plots spread on the left and top side, this means that the higher the percentage of the less of midwives in primary health care, the lower complete basic immunization coverage in the province of Indonesia (Figure 2). This is in line with previous research which stated that the higher a person's income level, the higher the chance for complete basic immunization (Debie et al, 2020;Fenta et al, 2021). Immunization coverage gaps due to income-based inequality were widened by maternal education and place of residence (Sharma et al, 2021).…”
Section: Correlation Between Poor Population and Complete Basic Immunizationsupporting
confidence: 90%
See 1 more Smart Citation
“…The scatter plot results show that the plots spread on the left and top side, this means that the higher the percentage of the less of midwives in primary health care, the lower complete basic immunization coverage in the province of Indonesia (Figure 2). This is in line with previous research which stated that the higher a person's income level, the higher the chance for complete basic immunization (Debie et al, 2020;Fenta et al, 2021). Immunization coverage gaps due to income-based inequality were widened by maternal education and place of residence (Sharma et al, 2021).…”
Section: Correlation Between Poor Population and Complete Basic Immunizationsupporting
confidence: 90%
“…The percentage of poor people in September 2018 was 9.66%, has decreased to 9.41% in March 2019 (Ministry of Health in Indonesia, 2020). The higher the income level of a person, the higher the chance to complete basic immunization (Debie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ethiopian demographic and health survey (EDHS) report, there is an improvement in complete basic childhood vaccination representing one dose of BCG, three doses of pentavalent (DPT-HepB-Hib), three doses of polio, and one dose of measles vaccine among children aged 12-23 months in the country, increased from 24% in 2011, 39% in 2016, to 44% in 2019 [14][15][16]. However, complete basic childhood vaccination status is yet very low compared with the national (at least 90% nationally with 80% in each district) and WHO (> = 90%) targets [17].…”
Section: Introductionmentioning
confidence: 99%
“…The highest coverage of full vaccination in Addis Ababa (83%) and lowest in Afar region due to different challenges and opportunities as explained in other studies (20%) (5,13). Studies have also reported that maternal education, place of delivery, antenatal care (ANC) visits, postnatal care follow up, place of residence and exposure to mass media as predictors of poor child immunization status (13,14,17,19). However, most of the studies were cross-sectional and failed to include certain variables or factors that could be pertinent in the Ethiopian context, such as socioeconomic status, attitude and service satisfaction towards immunization services provision at grassroots of individual family members and few community-based studies are available.…”
Section: Introductionmentioning
confidence: 89%